Gender Influence on Students Attitude Towards the Use of Scramble Game for Learning in Secondary School English Language Concepts in Ilorin Metropolis - Daramola, F. O. (Indonesian Journal Of Educational Research and Review, 2022)
Scramble games offer intense mental activities that hone cognitive skills, apply economic principles, and enable language learning in the classroom. Despite the many benefits, the scramble game is challenging and time-consuming. Therefore, this study analyzes the effect of gender on students' attitudes towards scramble games. This study uses a descriptive research design using a quantitative survey method. Two research questions and one answer have been answered and tested, respectively. A total of three hundred and eighty-six (386) respondents were sampled randomly; the number of frequencies, percentages, and averages answered the quick questions tested using the t-test. This finding concludes that gender affects students' attitudes towards using games for learning, among many others. Academic performance in English vocabulary can be improved by using the Scrabble game through students' mental activities while playing games. Likewise, the use of the game Scrabble in teaching English is learner-friendly and gender-friendly. The study recommends that students be encouraged to explore the full benefits of scramble games to enhance active classroom teaching.